A Micro-Decomposition Analysis of The Macroeconomic Determinants of Human Development - Lambert, Sylvie (The World Bank, 2007)
This paper shows how differences in aggregate human development outcomes over time and space can be additively decomposed into a pure economic-growth component, a component attributed to differences in the distribution of income, and components attributed to "non-income" factors and differences in the model linking outcomes to income or non-income characteristics. The income effect at the micro level is modeled non-parametrically, so as to flexibly reflect distributional changes. The paper illustrates the decomposition using data for Morocco and Vietnam, and the results offer some surprising insights into the observed aggregate gains in schooling attainments. A user friendly STATA program is available to implement the method in other settings